A Novel Encryption Scheme over Group Codes using Vigenère Cipher (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the rapid growth in technology there is an imperishable need for maintaining security and integrity of data while communication. These needs can be met by the advancements in the field of cryptography which can be achieved using the concepts of Coding theory, Linear Algebra and Number Theory. In this paper we propose a mechanism where characters are assigned code words using an encoding function and encryption is performed using the concept of Vigenere cipher over group codes..